Geological effects on water quality: a review of issues and challenges in Malaysia - Garba, Terfa E.; Reena L. Richard; Nor Ezzawanis A. Thani; Mohamad Azlan A. Majid; Mutari Lawal; Yelwa, Nura A. (Penerbit Universiti Kebangsaan Malaysia, 2021)
Malaysian source of water for household and industrial use is derived mainly from surface sources. The increasing demand for quality water for household consumption and industrial use has posed a great challenge to the otherwise abundant but scarce natural resources. This paper examines the important challenges associated with the deteriorating water quality in Peninsular Malaysia. Quality water enhances one’s good health. Therefore, evaluating health risk as a result of heavy metals introduction through drinking water from various geological activities like the ex-mining ponds in Klang Valley is worthy to note. Heavy metals which are one of the sources of contaminants, due to their solubility are transported from their source (mining, agricultural, and industrial) to groundwater. There is a linkage between land-use change (activities) such as logging, agriculture, urbanization, mining, and industrial activities as a potential source of contaminants, this is further conflated by the hydrogeology of the areas which show a shallow aquifer system predominantly associated with alluvial and carbonate. Also, microbial contamination had affected water sources. Given that more of the aquifer systems in Peninsular Malaysia are shallow, this makes it very easy for groundwater sources around Malaysia to be contaminated. The industrialisation and urbanisation in Malaysia, as well as the growing population, posed a great challenge to water quality. This paper highlights the key challenges and possible solutions to water quality management in Malaysia.